Method for recovering lactic acid alkyl ester through catalytic alcoholysis of polylactic acid

By using nanometal oxide dispersions as catalysts, the problems of high catalyst cost and long reaction time in the existing PLA chemical recovery methods are solved, and the rapid degradation and high yield of PLA are achieved, which is suitable for industrial applications.

CN119859098APending Publication Date: 2025-04-22BEIJING UNIV OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311368692.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the existing PLA chemical recycling methods, the catalyst preparation is complex, expensive, long reaction time, low yield, and the use of toxic solvents limits its industrial applications.

Method used

Nano-metal oxide dispersion is used as a phony homogeneous catalyst to catalyze PLA degradation through alcoholylation reaction, with small amount of catalyst usage and low cost, and can quickly depolymerize PLA under mild conditions and realize the recycling and utilization of the catalyst.

Benefits of technology

The rapid degradation of PLA is achieved, the yield of alkyl lactate is greater than 90%, the catalyst can be recycled and has no metal residue, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859098A_ABST
    Figure CN119859098A_ABST
Patent Text Reader

Abstract

The invention discloses a method for recovering lactic acid alkyl ester by catalyzing alcoholysis of polylactic acid. The method comprises the following steps: S1, putting PLA, a reaction solvent and a nano metal oxide dispersion into a reaction kettle; s2, after the degradation reaction is finished, carrying out suction filtration and recovery to obtain unreacted PLA and filtrate, drying a solid filter cake, weighing and calculating to obtain the degradation rate of the PLA, treating the filtrate, carrying out high performance gas chromatography, and calculating and measuring the product yield; s3, recovering the catalyst in the filtrate, and recycling the catalyst along with the reaction solvent in the depolymerization reaction; and distilling under reduced pressure and collecting products. When the dispersion catalyst is used for catalytically degrading the PLA, even if the dosage of the catalyst is only 0.5%, the PLA can be completely degraded within 15 minutes, and the yield of the product alkyl lactate is greater than 90%. The catalyst can be recycled, the product has no metal residue, and the method has good industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical recycling of waste bio-based plastics; more specifically, it relates to a method for recycling alkyl lactate by catalyzing alcoholysis of polylactic acid using nano metal oxide dispersion. Background Art

[0002] Petroleum-based plastics provide convenience for human life, but due to their non-degradability, discarded petroleum-based plastics can cause great harm to the environment and organisms, and destroy the ecological balance. Polylactic acid (PLA) is a high-molecular polyester material with excellent performance. It has the advantages of good biocompatibility, processability, biodegradability, environmental friendliness, and excellent physical properties. It is a potential substitute for petroleum-based polymer materials such as polyethylene, polypropylene and polystyrene. It can effectively alleviate the problems of energy shortage and "white pollution" and can be widely used in medical, textile and agricultural engineering. Although PLA is a biodegradable plastic, it takes three to six months to degrade even in the most suitable degradation environment. It may take decades for PLA to completely degrade on land, and the degradation rate in seawater is even lower. A large amount of waste PLA accumulation will still cause plastic pollution; in addition, the weight percentage of carbon element in PLA is about 50.4%, which is a good carbon source material. If it is directly degraded into CO2 and water after treatment, it is also a waste of resources (Sus.Chem.2020,1,1-22). Therefore, the recycling of PLA is still a very important step in the treatment of waste PLA.

[0003] At present, the chemical recycling methods of PLA mainly include pyrolysis, alcoholysis and hydrolysis. By chemical means, the waste polymers are cracked into small molecules with a certain purity and practical value. It is one of the effective ways to solve the problem of waste plastic pollution. These methods can achieve chemical depolymerization and recycling of PLA. Alcoholysis is currently recognized as the most suitable method for PLA chemical upgrading. The generated alkyl lactate is an important type of environmentally friendly chemical product. Due to its low toxicity and solvent properties, it is known as one of the most promising substitutes for petrochemical solvents. Among them, methyl lactate and ethyl lactate are widely used (Chem. Eng. J. 2022, 446, 136881). In nature, hydrolysis is the main method in the early degradation stage of PLA. Acid-base catalysts can effectively shorten the PLA hydrolysis reaction time. Under the conditions of 180°C and 1.5 MPa, the conversion rate of PLA reaches 98.15% after about 3 hours of hydrolysis. After adding 0.6 mol / L sodium hydroxide, the PLA degradation rate can reach 100% in only 20 minutes (Ind. Eng. Chem. Res. 2010, 49, 1247-1251).

[0004] At present, the catalysts used for PLA alcoholysis and hydrolysis are mainly strong acids or strong bases. The disadvantages are: large amount of catalysts, cannot be reused, severe corrosiveness, etc., which hinder the development of PLA degradation. With the deepening of research on reaction catalysts, the catalysts currently used for PLA depolymerization reactions are mainly homogeneous catalysts such as ionic liquids and metal complex catalysts. Ionic liquids have been used for polyester degradation due to their unique thermal stability and low volatility; metal complex catalysts have become one of the main catalysts for degrading PLA due to their high catalytic efficiency, low cost, and reusability.

[0005] In the Chinese invention patent publication with publication number CN 110003009 A, a method for recovering methyl lactate by catalyzing alcoholysis of waste polylactic acid with immobilized ionic liquid is disclosed, but the catalyst used in this method is expensive (GreenChem, 2018, 20, 1205). Due to the high price and large amount of such catalysts, their industrial application is limited.

[0006] Song et al. used [Bmim][OAc] as a catalyst. At 130°C, the degradation rate of PLA in water after 2 hours of reaction reached 93.93% (Polym.Degrad.Stab.2014,110,65-70). Payne et al. used Zn(II) complex as a catalyst. PLA was reacted in tetrahydrofuran (THF) and methanol at 80°C for 8 hours. PLA was completely depolymerized and the yield of methyl lactate reached 60% (Polym.Chem.2021,12,1086-1096). However, the long reaction time and low yield of this type of catalyst are still problems that need to be solved when it is applied to PLA degradation, and the use of THF, dichloromethane, acetone, etc. as solvents will cause harm to the environment.

[0007] Therefore, it is of great significance to improve the existing chemical recycling methods, reduce the drawbacks of the existing processes, and realize the green chemical recycling of waste PLA materials. Summary of the invention

[0008] Aiming at the shortcomings of the prior art, namely, the complex preparation of catalysts, high prices, long reaction time, low yield, and the use of organic toxic solvents other than alcohol and water, the technical problem to be solved by the present invention is to provide a method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid. The method adopts ultra-small-sized nano-dispersions as pseudo-homogeneous catalysts, and its heterogeneity not only improves the catalytic efficiency, but also combines the advantages of heterogeneous catalysis and homogeneous catalysis. The catalyst is used to catalyze the degradation of PLA. Even if the amount of the catalyst is only 0.5%, PLA can be completely degraded within 15 minutes, and the yield of the product alkyl lactate is greater than 90%. The catalyst can be recycled, and the product has no metal residue, which has good industrial application value.

[0009] To solve the above technical problems, the technical solutions adopted are as follows :

[0010] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0011] S1, placing PLA, reaction solvent, and nano-metal oxide dispersion into a reaction kettle;

[0012] S2. After the degradation reaction is completed, unreacted PLA and filtrate are recovered by suction filtration, the solid filter cake is dried, and the degradation rate of PLA is calculated by weighing. The filtrate is treated and analyzed by high performance gas chromatography to calculate the product yield;

[0013] S3, recovering the catalyst in the filtrate and recycling it with the reaction solvent in the depolymerization reaction; and collecting the product by vacuum distillation.

[0014] As a further improvement of the technical solution, in step S1, the nano metal oxide is selected from one or more of ZnO, CuO, Cu2O, TiO2, Fe3O4, ZrO2, and CeO2.

[0015] Preferably, in step S1, the amount of the nano metal oxide used in the depolymerization reaction is 0.05-1wt% of the mass of PLA, and more preferably, the amount is 0.25-0.5wt%.

[0016] Preferably, in step S1, the reaction solvent is selected from one or more of methanol, ethanol, ethylene glycol, 1,3-propylene glycol, and 1,4-butanediol.

[0017] Preferably, in step S1, the mass ratio of the reaction solvent to the PLA waste is 6-14:1; more preferably, the mass ratio is 8-12:1.

[0018] Preferably, in step S1, the heating temperature is 90-120°C, and the reaction time is 5-60 min; more preferably, in step S1, the heating temperature is 110°C, and the reaction time is 15-30 min.

[0019] Preferably, in step S1, stirring is performed during the reaction process, and the stirring speed of the reactor is 30-700 r / min; more preferably, the stirring speed is 300-500 r / min.

[0020] As a further improvement of the technical solution, in step S2, the temperature of the filtration after the depolymerization reaction is completed is 25-80°C; more preferably, the filtration temperature is 25-50°C.

[0021] As a further improvement of the technical solution, in step S3, the catalyst in the recovered filtrate is evaporated at a temperature of 30-70° C. for a time of 30-90 min.

[0022] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0023] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention uses nano-metal oxide dispersion as a catalyst to degrade PLA. The raw materials for catalyst synthesis are commercially available, the preparation process is simple, the cost is low, the amount used in the degradation process is small, and it has broad application prospects;

[0026] 2. The present invention uses nano-metal oxide dispersion as a catalyst to catalyze the alcoholysis of PLA, and rapidly depolymerizes PLA under mild conditions. Under preferred conditions, the PLA degradation rate reaches 100%, and the yield of the degradation product alkyl lactate can reach more than 90%. The degradation process is environmentally friendly and no metal residues are left.

[0027] 3. The catalyst can be recycled and has a good cyclic depolymerization effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0029] Figure 1 Transmission electron microscopy images of methanol-phase nano ZnO used in Examples 1 to 5;

[0030] Figure 2 This is the XRD pattern of the nano ZnO used in Example 1;

[0031] Figure 3 FT-IR diagram of the product obtained in Example 1;

[0032] Figure 4 This is a transmission electron microscopy image of ethanol-phase nano-ZnO used in Example 6;

[0033] Figure 5 A physical picture of the black PLA 3D printing consumables used in Example 8;

[0034] Figure 6 This is a physical picture of the 40 μm PLA film used in Example 9; DETAILED DESCRIPTION

[0035] In order to explain the present invention more clearly, the present invention is further described below in conjunction with embodiments. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0036] The PLA raw material used in the following examples was purchased from Dongguan Dihua Engineering Plastics Co., Ltd. The PLA model was 2500HP, the detected relative viscosity was 4.0, and the molecular weight was 70,000-80,000.

[0037] The black PLA 3D printing consumables used in Example 8 were purchased from Cixi Lanbo Printing Consumables Co., Ltd., with a wire diameter of 1.75 mm and a polylactic acid content of 90%.

[0038] The PLA 40um film used in Example 9 was purchased from Hubei Ruisheng New Materials Co., Ltd., and the polylactic acid content was 98%.

[0039] As one aspect of the present invention, a method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid comprises the following steps:

[0040] S1, placing PLA, reaction solvent, and nano-metal oxide dispersion into a reaction kettle;

[0041] S2. After the degradation reaction is completed, unreacted PLA and filtrate are recovered by suction filtration, the solid filter cake is dried, and the degradation rate of PLA is calculated by weighing. The filtrate is treated and analyzed by high performance gas chromatography to calculate the product yield;

[0042] S3, recovering the catalyst in the filtrate and recycling it with the reaction solvent in the depolymerization reaction; and collecting the product by vacuum distillation.

[0043] In the present invention, the nano metal oxide catalyst is a nano metal oxide stably and evenly dispersed in a liquid medium to form a pseudo-homogeneous nano metal oxide catalyst, and the liquid medium is selected from the reaction solvent in step S1. (The method for preparing the nano metal oxide dispersion is a method for preparing a transparent zinc oxide liquid dispersion disclosed in CN109181367A) The average particle size of the nano metal oxide in the dispersion is between 1-50nm, and the content of the nano metal oxide in the dispersion system is 1-30wt%.

[0044] In certain embodiments of the present invention, in step S1, the nano metal oxide is selected from one or more of ZnO, CuO, Cu2O, TiO2, Fe3O4, ZrO2, and CeO2.

[0045] In certain embodiments of the present invention, in step S1, the amount of the nano metal oxide used in the depolymerization reaction is 0.05-1 wt% of the mass of the PLA waste, and more preferably, the amount is 0.25-0.5 wt%.

[0046] In certain embodiments of the present invention, in step S1, the reaction solvent is selected from one or more of methanol, ethanol, ethylene glycol, 1,3-propylene glycol, and 1,4-butanediol.

[0047] In certain embodiments of the present invention, in step S1, the mass ratio of the reaction solvent to PLA is 6-14:1; more preferably, the mass ratio is 8-12:1.

[0048] In certain embodiments of the present invention, in step S1, the heating temperature is 90-120°C, and the reaction time is 5-60 min; more preferably, in step S1, the heating temperature is 110°C, and the reaction time is 15-30 min.

[0049] In certain embodiments of the present invention, in step S1, stirring is performed during the reaction process, and the stirring speed of the reactor is 30-700 r / min; more preferably, the stirring speed is 300-500 r / min.

[0050] In certain embodiments of the present invention, in step S2, the temperature of the filtration after the depolymerization reaction is completed is 25-80°C; more preferably, the filtration temperature is 25-50°C.

[0051] In certain embodiments of the present invention, in step S3, the catalyst in the filtrate is recovered at a rotary evaporation temperature of 30-70° C. and a rotary evaporation time of 30-90 min.

[0052] Example 1

[0053] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0054] 1) 0.27 g ZnO methanol phase dispersion (solid content 10.1 wt%), 5.5 g PLA particles (diameter 3 mm) and 55 g methanol were weighed and added into a reaction kettle, mixed and stirred evenly, the kettle cover was sealed, and the reaction was carried out at 110° C. for 15 min under magnetic stirring at 500 rpm.

[0055] 2) After the reaction is completed, the reaction liquid is filtered at room temperature, and the filter cake obtained is unreacted PLA. It is washed three times with deionized water and dried in a vacuum drying oven for 24 hours. The mass is weighed and the PLA degradation rate is calculated to be 100%; the filtered reaction liquid is treated and analyzed by high performance gas chromatography, and the yield of methyl lactate is 95.3%;

[0056] 3) The catalyst can be recovered by rotary evaporation of the filtrate.

[0057] Example 2

[0058] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0059] 1) Weigh 0.27 g ZnO methanol phase dispersion (solid content 10.1 wt%), 5.5 g PLA particles (diameter 3 mm) and 55 g methanol into a reaction kettle, mix and stir evenly, seal the kettle cover, and react at 110° C. for a certain time (specific time is shown in Table 1 below) under magnetic stirring at 500 rpm;

[0060] 2) After the reaction is completed, the reaction liquid is filtered at room temperature, and the filter cake obtained is unreacted PLA. After washing three times with deionized water, it is dried in a vacuum drying oven for 24 hours, and its mass is weighed to calculate the degradation rate of PLA; the filtered reaction liquid is treated and analyzed by high performance gas chromatography to obtain methyl lactate, and the yield is shown in Table 1 below;

[0061] 3) The catalyst can be recovered by rotary evaporation of the filtrate.

[0062] The PLA degradation rate and methyl lactate (MeLA) yield of this embodiment are shown in Table 1:

[0063] Table 1 PLA degradation rate and MeLA yield

[0064] Reaction time PLA degradation rate MeLA yield 15min 100% 95.1% 30min 100% 95.7% 45min 100% 98.6% 60min 100% 98.7%

[0065] Example 3

[0066] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0067] 1) Weigh 0.27 g ZnO methanol dispersion (solid content 10.1 wt%), 5.5 g PLA particles (diameter 3 mm) and 44 g-66 g methanol into a reactor, mix and stir evenly, seal the reactor lid, and react at 110° C. for 15 min under magnetic stirring at 500 rpm;

[0068] 2) After the reaction is completed, the reaction liquid is filtered at room temperature, and the filter cake obtained is unreacted PLA. It is washed three times with deionized water and dried in a vacuum drying oven for 24 hours. The mass is weighed and the PLA degradation rate is calculated to be 100%; the filtered reaction liquid is treated and analyzed by high performance gas chromatography, and the yield of methyl lactate is 90.1%-95.3%;

[0069] 3) The catalyst can be recovered by rotary evaporation of the filtrate.

[0070] Example 4

[0071] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0072] 1) Weigh 0.27 g ZnO methanol dispersion (solid content 10.1 wt%), 5.5 g PLA particles (diameter 3 mm) and 55 g methanol into a reactor, mix and stir evenly, seal the reactor lid, and react at 110° C. for 15 min under magnetic stirring at 500 rpm;

[0073] 2) After the reaction is completed, the reaction liquid is filtered at room temperature, and the filter cake obtained is unreacted PLA. It is washed three times with deionized water and dried in a vacuum drying oven for 24 hours. The mass is weighed and the degradation rate of PLA is calculated. The filtered reaction liquid is treated and analyzed by high performance gas chromatography to obtain the yield of methyl lactate;

[0074] 3) The catalyst can be recovered from the rotary evaporation filtrate and used for the next PLA degradation reaction under the same conditions. The degradation process is carried out 5 times in total.

[0075] The degradation rate of PLA and the yield of methyl lactate (MeLA) are shown in Table 2:

[0076] Table 2 PLA degradation rate and MeLA yield

[0077] Number of cycles PLA degradation rate MeLA yield 1 100% 95.6% 2 100% 93.3% 3 99.7% 90.2% 4 99.3% 86.6% 5 98.9% 80.1%

[0078] Example 5

[0079] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0080] 1) 0.24 g ZnO ethanol dispersion (solid content 11.3 wt%), 5.5 g PLA particles (diameter 3 mm) and 55 g ethanol were added to a reaction kettle, the kettle cover was sealed, and the reaction was carried out at 130° C. for 15 min under magnetic stirring at 500 rpm;

[0081] 2) After the reaction is completed, the reaction liquid is filtered at room temperature, and the filter cake obtained is unreacted PLA. It is washed three times with deionized water and dried in a vacuum drying oven for 24 hours. The mass is weighed and the PLA degradation rate is calculated to be 100%; the filtered reaction liquid is treated and analyzed by high performance gas chromatography, and the yield of ethyl lactate is 91.7%;

[0082] 3) The catalyst can be recovered by rotary evaporation of the filtrate.

[0083] Example 6

[0084] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0085] 1) 0.74 g ZnO ethylene glycol phase dispersion (solid content 3.7 wt%), 5.5 g PLA particles (diameter 3 mm) and 55 g ethylene glycol were added to a reaction kettle, the kettle cover was sealed, and the reaction was carried out at 180° C. for 30 min under magnetic stirring at 500 rpm;

[0086] 2) After the reaction is completed, the reaction liquid is filtered at room temperature, and the filter cake obtained is unreacted PLA, which is washed three times with deionized water and dried in a vacuum drying oven for 24 hours. The mass is weighed, and the PLA degradation rate is calculated to be 100%; the filtered reaction liquid is treated and analyzed by nuclear magnetic resonance hydrogen spectrum, and the yield of the product ethylene glycol monolactate is 92.4%;

[0087] 3) The catalyst can be recovered by rotary evaporation of the filtrate.

[0088] Example 7

[0089] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0090] 1) 0.32 g of CuO methanol dispersion (solid content 8.7 wt%), 5.5 g of PLA particles (diameter 3 mm) and 55 g of methanol were added to a reaction kettle, the kettle cover was sealed, and the reaction was carried out at 110° C. for 30 min under magnetic stirring at 500 rpm;

[0091] 2) After the reaction is completed, the reaction liquid is filtered at room temperature, and the filter cake obtained is unreacted PLA. It is washed three times with deionized water and dried in a vacuum drying oven for 24 hours. The mass is weighed and the PLA degradation rate is calculated to be 100%; the filtered reaction liquid is treated and analyzed by high performance gas chromatography, and the yield of methyl lactate is 92.3%;

[0092] 3) The catalyst can be recovered by rotary evaporation of the filtrate.

[0093] Example 8

[0094] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0095] 1) Weigh 0.27 g ZnO methanol phase dispersion (solid content 10.1 wt%), 5.5 g black PLA 3D consumables (length 2 cm) and 55 g methanol into a reactor, mix and stir evenly, seal the reactor lid, and react at 110° C. for 15 min under magnetic stirring at 500 rpm.

[0096] 2) After the reaction is completed, the reaction liquid is filtered at room temperature. The filter cake obtained is the unreacted material. It is washed three times with deionized water and dried in a vacuum drying oven for 24 hours. The mass is weighed and the degradation rate is calculated to be 92.6%; the filtered reaction liquid is treated and analyzed by high performance gas chromatography, and the yield of methyl lactate is 60.3%;

[0097] 3) The catalyst can be recovered by rotary evaporation of the filtrate.

[0098] Example 9

[0099] A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, comprising the following steps:

[0100] 1) 0.27 g ZnO methanol phase dispersion (solid content 10.1 wt%), 5.5 g PLA film (size 1 cm×1 cm) and 55 g methanol were weighed and added into a reaction kettle, mixed and stirred evenly, the kettle cover was sealed, and the mixture was reacted at 110° C. for 15 min under magnetic stirring at 500 rpm.

[0101] 2) After the reaction is completed, the reaction liquid is filtered at room temperature. The filter cake obtained is the unreacted material. It is washed three times with deionized water and dried in a vacuum drying oven for 24 hours. The mass is weighed and the degradation rate is calculated to be 97.5%; the filtered reaction liquid is treated and analyzed by high performance gas chromatography, and the yield of methyl lactate is 90.9%;

[0102] 3) The catalyst can be recovered by rotary evaporation of the filtrate.

[0103] Comparing Example 8 and Example 9, it can be seen that the polylactic acid content in the degraded 3D consumables in Example 8 is only 90%, and there are also modifiers, plasticizers, colorants and other substances, which affect the yield of the degradation product methyl lactate and significantly reduce it. The PLA film degraded in Example 9 has a high polylactic acid content and a low content of additives such as modifiers and plasticizers, so that the yield of the degradation product is >90%.

[0104] Comparative Example 1

[0105] Example 1 was repeated, except that in step 1), the reaction temperature in the reactor was 105° C., the PLA degradation rate after the reaction was 99.5%, and the product yield was 73.51%.

[0106] It can be seen that when the reaction temperature is slightly lower, the yield of degradation products is greatly reduced.

[0107] Comparative Example 2

[0108] Example 1 was repeated, except that in step 1), the reaction temperature in the reactor was 115° C., the PLA degradation rate after the reaction was 100%, and the product yield was 56.71%.

[0109] It can be seen that when the reaction temperature is slightly higher, the yield of degradation products is greatly reduced.

[0110] Comparative Example 3

[0111] Example 1 was repeated, except that in step 1), the amount of catalyst in the reactor was 0.14 g, the PLA degradation rate after the reaction was 64.3%, and the product yield was 32.8%.

[0112] It can be seen that when the mass ratio of the catalyst dosage to PLA in the reactor is less than 0.50%, the PLA degradation rate and product yield are greatly reduced.

[0113] Comparative Example 4

[0114] Example 1 was repeated, except that in step 1), the amount of catalyst in the reactor was 0.41 g, the PLA degradation rate after the reaction was 100%, and the product yield was 67.3%.

[0115] It can be seen that when the mass ratio of the catalyst dosage to PLA in the reactor is greater than 0.50%, the product yield is still greatly reduced.

[0116] Comparative Example 5

[0117] Example 2 was repeated, except that in step 1), the reaction time in the reactor was 10 min, the PLA degradation rate after the reaction was 100%, and the product yield was 66.3%.

[0118] It can be seen that when the reaction time in the reactor is less than 15 min, the product yield will be greatly reduced.

[0119] Comparative Example 6

[0120] Example 4 was repeated, except that in step 1), the amount of methanol in the reactor was 33 g, the PLA degradation rate after the reaction was 99.2%, and the product yield was 76.3%.

[0121] It can be seen that when the amount of methanol in the reactor is too low, the product yield will be greatly reduced.

[0122] Comparative Example 7

[0123] Example 4 was repeated, except that in step 1), the amount of methanol in the reactor was 66 g, the PLA degradation rate after the reaction was 100%, and the product yield was 79.4%.

[0124] It can be seen from this that when the amount of methanol in the reactor is too high, the product yield will still be greatly reduced.

[0125] Comparative Example 8

[0126] Example 1 was repeated, except that in step 1), the reaction temperature was 110° C., and the reaction was carried out without stirring. After the reaction, the PLA degradation rate was 76%, and the product yield was 72%.

[0127] It can be seen that when there is no stirring in the reactor, the PLA degradation rate and product yield will be greatly reduced.

[0128] Comparative Example 9

[0129] Example 1 was repeated, except that: in step 2), the filtration at room temperature was performed while hot (>70° C.), and the PLA degradation rate after the reaction was 98%, and the product yield was 79%.

[0130] It can be seen that in step 2), the temperature of the filtration has a great influence on the product yield.

[0131] Obviously, the above embodiments and comparative examples of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid, characterized in that: The following steps are involved: S1, placing PLA, reaction solvent, and nano-metal oxide dispersion into a reaction kettle; S2. After the degradation reaction is completed, unreacted PLA and filtrate are recovered by suction filtration, the solid filter cake is dried, and the degradation rate of PLA is calculated by weighing. The filtrate is treated and analyzed by high performance gas chromatography to calculate the product yield; S3, recovering the catalyst in the filtrate and recycling it with the reaction solvent in the depolymerization reaction; and collecting the product by vacuum distillation.

2. The method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid according to claim 1, characterized in that: In step S1, the nano metal oxide is selected from one or more of ZnO, CuO, Cu2O, TiO2, Fe3O4, ZrO2, and CeO2.

3. The method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid according to claim 1, characterized in that: In step S1, the amount of the nano metal oxide used in the depolymerization reaction is 0.05-1wt% of the mass of PLA, and more preferably, the amount is 0.25-0.5wt%.

4. The method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid according to claim 1, characterized in that: In step S1, the reaction solvent is selected from one or more of methanol, ethanol, ethylene glycol, 1,3-propylene glycol, and 1,4-butanediol.

5. The method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid according to claim 1, characterized in that: In step S1, the mass ratio of the reaction solvent to the PLA waste is 6-14:1; more preferably, the mass ratio is 8-12:

1.

6. The method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid according to claim 1, characterized in that: In step S1, the heating temperature is 90-120°C, and the reaction time is 5-60 min; more preferably, in step S1, the heating temperature is 110°C, and the reaction time is 15-30 min.

7. The method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid according to claim 1, characterized in that: In step S1, stirring is performed during the reaction process, and the stirring speed of the reactor is 30-700 r / min; more preferably, the stirring speed is 300-500 r / min.

8. The method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid according to claim 1, characterized in that: In step S2, after the depolymerization reaction is completed, the filtration temperature is 25-80°C; more preferably, the filtration temperature is 25-50°C.

9. The method for recovering alkyl lactate by catalytic alcoholysis of polylactic acid according to claim 1, characterized in that: In step S3, the catalyst in the filtrate is recovered, the rotary evaporation temperature is 30-70° C., and the rotary evaporation time is 30-90 min.

Citation Information

Patent Citations

  • Method used for preparing transparent zinc oxide liquid phase dispersion

    CN109181367A

  • Method for recovering methyl lactate by using supported ionic liquid for catalyzing alcoholysis of waste polylactic acid

    CN110003009A